Metastatic Pattern, Local Relapse, and Survival of Patients with Myxoid Liposarcoma: A Retrospective Study of 45 Patients. (20th June 2013) - Fuglø, Hanna M.; Maretty-Nielsen, Katja; Hovgaard, Dorrit; Keller, Johnny Ø.; Safwat, Akmal A.; Petersen, Michael M.
Abstract : Purpose . To assess the metastatic pattern of the histological subtype myxoid liposarcoma (MLS) with no or few round cells. Methods . Forty-five patients (F/M = 27/18, mean age 49 (range 17–85) years) were diagnosed with MLS at two Danish sarcoma centres in the period 1995–2004. A retrospective review of patients' files combined with an extraction of survival data from the Danish Centralised Civil Register was performed. Results . Seven patients had distant metastases during the observation period. Two patients had metastases at the time of diagnosis, while metastases occurred within 2.5 years in four patients, and in one patient 11.9 years after primary diagnosis. All metastases occurred at extrapulmonary sites. The first local relapse occurred within 3 years after surgery in six patients, in one patient after 4.0 years, and in one patient 7.7 years after surgery. The 5- and 10-year overall survival was 80% and 69%, respectively. Both the 5- and 10-year distant metastases-free survival was, respectively, 86%. The 5- and 10-year local relapse-free survival was, respectively, 83% and 80%. Conclusions . Patients with MLS had only extra-pulmonary metastases, and no lung metastases were found. Most local relapses and distant metastases occurred within the first 2-3 years after surgery.